The effects of UV-C on production of hypericin, phenolic and flavonoid in Hypericum triquetrifolium Turra - Toker, Zuhal; Karakaş, Özgür; Özen, Hasan Çetin (RESEARCH JOURNAL BIOTECHNOLOGY, 2015)
The current study was undertaken to determine the effects of UV-C radiation of total hypericin, phenolic and flavonoid content in Hypericum triquetrifolium Turra. The UV-C radiation was applied to H. triquetrifolium at different periods (15, 30, 45, 60 min). The highest total hypericin, phenolic and flavonoid accumulation 292 +/- 2.8, 357 +/- 3.4 and 331 +/- 3.7 mu gg(-1) was achieved in 15 minutes of exposure to UV-C radiation when compared with the contents of control groups (140 +/- 2.3, 185 +/- 3.7, 173 +/- 2.5 mu gg(-1)).
Keywords: Hypericum triquetrifolium Turra; Hypericin; Phenolics; Flavonoids; UV-C